Delayed spontaneous recanalization of chronic total occlusion of left anterior descending artery after attempted but failed revascularization during percutaneous coronary intervention. Issue 4 (4th July 2018) - Guragai, Nirmal; Rampal, Upamanyu; Vasudev, Rahul; Patel, Hiten; Manohar, Hashita Diana; Bhandari, Pragya; Bikkina, Mahesh; Shamoon, Fayez; Virk, Hartaj
ABSTRACT: Chronic total occlusion (CTO) of coronary artery remains the Achilles heel of the interventional cardiologist and is present in a significant proportion of referrals for coronary artery bypass graft surgery (CABG); however, with the development and standardization of modern CTO recanalization techniques, it has been able to achieve excellent success while coping with lesions of increasing complexity. Nevertheless, failure to recanalize despite the development of new techniques still remains one of the challenges in the field of interventional cardiology. Spontaneous recanalization has been described in nonocclusive coronary artery dissections in detail; none has addressed the possibility of spontaneous recanalization after failed percutaneous coronary intervention (PCI). We report a case of spontaneous but delayed recanalization of CTO of left anterior descending artery 3 years after attempted but failed revascularization during PCI.